Suspensão do contrato de trabalho na pandemia: estudo das aplicações práticas do Programa Emergencial de Manutenção do Emprego e da Renda da Lei 14.020/2020 - Freitas, Maria Eduarda Ribeiro de (Universidade do Vale do Rio dos Sinos, 2021)
This current paperwork aims at the study of the practical applications of the Job and Income Maintenance Emergency Program, introduced in the pandemic moment by the law number 14.020/2020, specifying, it has the intention of understanding how the reflexes of the suspension action, that the employment contract provided, must be conducted, since it has become a discussion trigger. Through the inductive method for the research, it has been sought to deal with current topics on a reflective way so that a critical view was built about the subject along with the presented authors. Starting there, it was noticeable that the COVID-19 pandemic enabled several legislation modifications, needed, facing the presented context. Mainly, the most affected area was the labor law, since the social distance conducted to several activities shutdowns, the ones which were not able to migrate to remote service. The JIMEP creation came as a loosen movement to companies and a relief to employees who feared the shutting down of workstations. Aiming to maintain occupational contracts and assure economic health of establishments, the program allowed the reduction of working time and suspension of employment contracts, in the meantime, the employee would receive assistance funded by public coffers. Throughout the paperwork, it was noticed that the program reached its goal, but facing the legislation omissions held in relation to the reflexes of the suspension action of employment contracts, a legislation remodeling was checked as necessary so that employees and employers would not suffer with uncertainties.
Keywords: Pandemia; Trabalho; Suspensão de contratos; Economia; Pandemic; Labor; Contract suspension; Economy